PILIHAN BAHASA PADA IKLAN LUAR RUANG DI KOTA BANJARMASIN - Yuliati Puspita Sari (Balai Bahasa Kalimatan Selatan, 2018)
The aim of this research is to describe variety of language choices on outdoors advertising in Banjarmasin and various factors causing the emergence of variety of language choices. The method used in this research is descriptive qualitative method. Advertisement language is different from language in scientific work. Advertisement language is short and easy to understand. The result shows that there are four varieties of language choices on outdoors advertising in Banjarmasin, namely (a) Indonesian language advertisement; (b) foreign language advertisement; (c) variety of local language adertisement; (d) mixed language advertisement. Meanwhile, there are six causes behind the emergence of variety of language choices on outdoors advertising in Banjarmasin, namely (a) the efforts to build closeness between advertisers and potential customers; (b) the effort to attract potential customers; (c) the effort to build a product image; (d) the use of foreign terms to be considered more concise than their counterparts in Indonesian language; (e) the advertiser selects a particular word to represent the product; and (f) the advertiser does not know or less attention about the indonesianizing foreign terms.